Drug-free gel containing ultra-deformable phospholipid vesicles (TDT 064) as topical therapy for the treatment of pain associated with osteoarthritis: a review of clinical efficacy and safety. (April 2014) - Conaghan, Philip G.; Bijlsma, Johannes W.; Kneer, Werner; Wise, Elspeth; Kvien, Tore K.; Rother, Matthias
Abstract Background: Many patients with osteoarthritis (OA) experience side effects with available systemic therapies, some of which can be life threatening. The widespread use of nonsteroidal anti-inflammatory drugs (NSAIDs), often without prescription, is concerning given their potential risks. New treatments for OA are therefore required. This review discusses evidence supporting the use of TDT 064, a drug-free, topical gel containing ultra-deformable phospholipid vesicles (Sequessome* vesicles), for OA-associated pain. Scope: Preclinical and clinical studies investigating TDT 064 in patients with OA-associated knee pain were identified in searches of PubMed and congress abstracts. Findings: The ultra-deformable phospholipid vesicles (sequessome vesicles) in TDT 064 pass through the skin intact to reach the synovial space within the joint. The mechanism of action is not yet certain, but the phospholipid-based structure of these ultra-deformable phospholipid vesicles, and the observation that they localize to the cartilage surface, support biolubrication as a possible mechanism of action of TDT 064. Data from randomized, phase III studies in OA knee pain in which TDT 064 was used as the drug-free vehicle control for IDEA-033 (ketoprofen in ultra-deformable phospholipid vesicles) demonstrate a marked and consistent response to TDT 064 in terms of pain, stiffness, and function. In a 12 week study of >1300 patients, the effects of TDT 064 on pain and function were statistically noninferior to those of oral celecoxib, and superior to oral placebo. TDT 064 was well tolerated in all studies, and adverse events were typically mild-to-moderate effects on the skin. Conclusions: Evidence from clinical studies supports the use of TDT 064 as a drug-free topical treatment for patients with OA. Further experience with TDT 064, particularly among patients with comorbidities or NSAID contraindications, will provide more information on its potential use.